Analisis Postur kerja pada Operator Stasiun Boiler Menggunakan Metode Rapid Upper Limb Assessement (RULA) - Ilham, Muhammad; Andriani, Meri (Jurnal Industri Samudra, 2024)
This study conducted a Posture Analysis on boiler operators using the Rapid Upper Limb Assessment (RULA) method. The purpose of this study is to determine what actions workers should take to avoid the risk of complaints and pain in the body of workers at a boiler station which has 4 workers. This study uses the Rapid Upper Limb Assessment (RULA) method to analyze the level of ergonomic risk of body areas that experience complaints or pain. the work posture of workers 1,2,3 and 4 got a score for worker 1 with a score of 8, for worker 2 with a score of 7, for worker 3 with a score of 8 and for worker 4 with a score of 8. The results of analyzing the work posture of the boiler operator got the results of the action on worker 1 with the description of the action right now, worker 2 with the description of the action right now, worker 3 with the description of the action right now and for worker 4 with the description of the action right now, The conclusion of the analysis can be concluded that the need for changes in work posture right now to avoid Fatigue and physical injury.